Toxicity characteristic leaching procedure over- or under-estimates leachability of lead in phosphate-amended contaminated soils. (November 2015) - Sima, Jingke; Cao, Xinde; Zhao, Ling; Luo, Qishi
Graphical abstract: The reaction process of Pb(NO3 )2 -contaminated soil amended by TSP: the concentrations of Pb and P in TCLP leachate decreased but Pb–P precipitates increased as leaching time increased. Highlights: Lead leachability does not reach equilibrium during the standard TCLP test. The acidic TCLP fluid induces more transformation of insoluble Pb–P precipitates. TCLP underestimates the leaching of soil Pb with less soluble PR amendment. TCLP overestimates the leaching of soil Pb with soluble TSP amendment. Abstract: In this study, Pb(NO3 )2 -, PbSO4 -, or PbCO3 -contaminated soils were treated with triple super phosphate (TSP) or phosphate rock (PR) and then subjected to the toxicity characteristic leaching procedure (TCLP) to assess Pb leachability. Soluble TSP resulted in the transformation of Pb into insoluble Pb phosphate precipitates in all contaminated soils, and the transformation increased with extended leaching times. Consequently, Pb concentrations in the TCLP leachates treated with TSP were reduced by 97.3–99.7% compared with the untreated soils, and Pb leaching decreased over the extraction time and did not reach equilibrium even after 96 h of extraction. Precipitation of Pb phosphate minerals in the less soluble PR-treated soil was limited, and Pb leaching was controlled by the dissolution of the Pb compounds, resulting in elevation of Pb in the TCLP leachate. Pb leaching continued to increase with time due to continuous dissolution of PbSO4 and PbCO3 . The results indicated that Pb leaching is kinetically controlled by either Pb compound dissolution or phosphate mineral formation. The standard TCLP test using a designated 18 h incubation time can overestimate the leachability of Pb in soils contaminated with lead and amended with soluble TSP and underestimate the leachability of Pb in soils contaminated with Pb and amended with less soluble PR. Therefore, wide use of TCLP for assessing Pb leachability in all contaminated soils is insufficient, and development of a site-specific evaluation method is urgently needed.